Vibration and Buckling Analysis of Skew Sandwich Plate using Radial Basis Collocation Method - Jigyasa Singh; Ram Prasad (Mechanics of Advanced Composite Structures)
This paper presents the free vibration and buckling responses of a skew sandwich plate using higher-order shear deformation theory (HSDT).  The governing differential equations (GDEs) for the skew sandwich plate are obtained using Hamilton's principle, which states that the actual motion of a system minimizes the total potential energy of the system. The GDEs obtained are discretized using radial basis function (RBF), which is a meshfree based numerical method. The vibration and buckling results for skew sandwich plates using meshfree methods and the effect of node distribution are not available in the open literature to the best of the author's knowledge. Numerous results are presented showing the non-dimensional frequency and buckling parameters of the skew sandwich plates for different values of the plate geometry, material properties, and boundary conditions. These results provide insights into the vibration and buckling behavior of skew sandwich plates and can be used to optimize the design and performance of these plates for various applications, such as aerospace structures, marine structures, and civil engineering structures. Convergence studies of present results are checked, and the results obtained are also validated with the results available in the open literature. The effect of span-to-thickness ratio, core-to-face thickness ratio, aspect ratio, boundary conditions, boundary node distribution, and skew angle is examined. The results presented in this paper can be useful for engineers and researchers working in the field of structural mechanics and can contribute to the development of safer and more efficient structures.